1984
DOI: 10.1071/mf9840793
|View full text |Cite
|
Sign up to set email alerts
|

Life histories of some benthic insects from the La Trobe River, Victoria

Abstract: The life histories of the following species were studied over 2 years at various sites throughout the catchment of the La Trobe River: Tasmanocoenis tonnoiri and Tasmanocoenis sp. (Ephemeroptera : Caenidae), Atalophlebioides sp. and two Atalonella spp. (Ephemeroptera : Leptophlebiidae), two Baetis spp. (Ephemeroptera : Baetidae), Leptoperla primitiva and L. neboissi (Plecoptera : Gripopterygidae), Cyphon sp. (Coleoptera : Helodidae), Ecnomus sp. (Trichoptera : Ecnomidae). The life cycles of these species varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
(26 reference statements)
0
28
0
1
Order By: Relevance
“…Only in spring (for both the edge and riffle habitats) did the average number of taxa recovered from Live-sort sub-samples exceed that from the Lab-sort sub-samples, so the efficiency of the Livesorting method in recovering taxa appears to depend on the season in which a sample is collected. Many insect taxa have seasonal life-cycles, and distinct changes in the size distribution of the aquatic larvae occur with time (Marchant et al, 1984;Yule, 1985;Dean & Cartwright, 1987). Many such insect larvae are represented by small early instars in autumn, but in spring they are more mature and, therefore, more conspicuous (Hynes, 1970).…”
Section: Discussionmentioning
confidence: 98%
“…Only in spring (for both the edge and riffle habitats) did the average number of taxa recovered from Live-sort sub-samples exceed that from the Lab-sort sub-samples, so the efficiency of the Livesorting method in recovering taxa appears to depend on the season in which a sample is collected. Many insect taxa have seasonal life-cycles, and distinct changes in the size distribution of the aquatic larvae occur with time (Marchant et al, 1984;Yule, 1985;Dean & Cartwright, 1987). Many such insect larvae are represented by small early instars in autumn, but in spring they are more mature and, therefore, more conspicuous (Hynes, 1970).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the seasonal temperature variation provides well defined cues for stream biota, and recruitment is often synchronous (Bunn 1988). Hydrology also plays an important role in shaping life histories (Resh et al 1988) and those of Australian stream invertebrates seem to be strongly influenced by the pattern of stream discharge (Marchant et al 1984;Bunn 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The harshness and uncertainty of the climate, together with the absence of a well-defined input of energy in the form of an autumn litter-fall, were considered to be indirectly responsible by giving rise to flexible life history patterns and broad niches of the species (Williams & Wan, 1972 ;Hynes & Hynes, 1975 ;Winterbourn, 1980) . Subsequent research, particularly in south-eastern Australia, has clearly demonstrated a highly seasonal litter-fall (Lake, 1982 ;Bunn, 1986a) and life histories that are perhaps more synchronized than previously thought (Marchant et al, 1984a ;Yule, 1985 ;Dean & Cartwright, 1987) . Furthermore, it is now evident that the fauna of these streams is not as depauperate as first suggested and may even be richer than comparable temperate Northern Hemisphere streams (Lake et al ., 1985).…”
Section: Introductionmentioning
confidence: 99%